An anthropological study on issues and challenges through ethnic conflict (With Special Reference to Mahakongaskada Village in Medawachchiya; Sri Lanka) - Samarasekara, S. (My University, 2019)
Sri Lanka is in a period of revival after the end of a civil war which was fought for several decades. The roots of this ethnic conflict traces back to certain administrative decisions of colonizers as well as of successive governments which expanded the conflict into a complete civil war between the Sinhala majority and the Tamil minority represented by the terrorist organization, the Liberation Tigers of Tamil Eelam. This study has been designed to explore and explain the impact of socio cultural change during civil war on individual’s daily routine, from an academic point of view and there ascertains the current situation with an in-depth analysis of the victim’s present and past way of life. The general objective of this study is to identify the pattern of socio cultural change while comparing the civil war period and its post conditions of the civilians. The research takes up mixed method approach on the basis of field research in Mahakongaskada village in Madawachchiya which has been done on scheduled interview method while using 150 households as the sample and to that end it gathers secondary sources that asses the post-war situation in Sri Lanka. The research findings manifest that internal and external factors affect to the alienation of individuals due to the sociocultural change in research area. Lack of social network and lack of supportive mechanism were identified as issues among villagers. Lack of transport and road network are major challenges to achieve the opportunities for the job market. Moreover, while the villagers were fluently speak both Sinhala and Tamil it’s difficult to get the jobs due to poor educational qualifications specially lack of knowledge in English as well as IT. Mass media usage is in a better situation while comparing to the civil war period. The conclusion of the research was rehabilitation and reconciliation process has to be regenerate while understanding the social and cultural change due to civil war. The remaining physical and sociocultural environment has proven that the victims were lost in sociocultural change with the scars of civil war even after ten years from the victory. Government and organizations should establish vocational training centers and skill develop programs in village level to recreate the social network and to give supportive mechanism to the victims.
Keywords: Sri Lanka, ethnic conflict, victims, reconciliation, sociocultural change